2019
DOI: 10.1007/s00592-019-01301-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of methicillin-resistant Staphylococcus aureus among diabetic patients: a meta-analysis

Abstract: Aims Diabetic patients have multiple risk factors for colonisation with methicillin-resistant Staphylococcus aureus (MRSA), a nosocomial pathogen associated with significant morbidity and mortality. This meta-analysis was conducted to estimate the prevalence of MRSA among diabetic patients. Methods The MEDLINE, Embase, BIOSIS, and Web of Science databases were searched for studies published up to May 2018 that reported primary data on the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 98 publications
5
54
1
1
Order By: Relevance
“…Antimicrobial resistance is a common finding in DFIs, with meta-analyses estimating the global prevalence of methicillin-resistant S. aureus in DFIs to be 15-30% [8,9]. Previous studies in the UK have reported higher rates, ranging from 19.9 to 57.9% [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial resistance is a common finding in DFIs, with meta-analyses estimating the global prevalence of methicillin-resistant S. aureus in DFIs to be 15-30% [8,9]. Previous studies in the UK have reported higher rates, ranging from 19.9 to 57.9% [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The microorganisms most commonly isolated from DFIs are aerobic Gram positive bacteria, predominantly Staphylococci [7,8]. The prevalence of methicillin resistant Staphylococcus aureus (MRSA) in DFIs is considered to be 15-30% [8,9]. Other bacterial genera commonly found in DFIs include Streptococci, Enterococci, Enterobacteriaceae, and Pseudomonas [3].…”
Section: Introductionmentioning
confidence: 99%
“…These infections are favored when there are abnormalities in defense mechanisms, when the patients have a chronic disease such as DM, and also when there are interruptions in the continuity of skin, such as ulcers [ 11 , 19 , 20 ]. Diabetic patients have multiple risk factors for colonization with methicillin-resistant Staphylococcus aureus (MRSA), a nosocomial pathogen associated with significant morbidity and mortality rates [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15–30% of the human population is colonized with Staphylococcus aureus [ 9 ]. Nevertheless, according to the meta-analysis by Stacey et al patients with diabetes have a 4.75% higher colonization rate than non-diabetic people [ 10 ]. Importantly, this bacterium causes a wide range of clinical infections (e.g., bacteremia, endocarditis, skin and soft tissue, osteoarticular, pulmonary, and device-related infections).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation